Refractory pemphigus vulgaris treated with rituximab and mycophenolate mofetil - Stephanie Del Rio Navarrete Biot; Joanna Pimenta de Araujo Franco; Ricardo Barbosa Lima; Henrique Novo Costa Pereira; Luiz Paulo José Marques; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2014)
The main treatment for pemphigus vulgaris are systemic corticosteroids and immunosuppressive agents, but due to adverse reactions and therapeutic failure, new drugs such as rituximab and mycophenolate mofetil have been used. In this case report are described two cases of severe pemphigus vulgaris refractory to various treatments, with resolution after use of rituximab and mycophenolate mofetil, associated with corticosteroids. A higher-than-usual dose of rituximab was employed, without the occurrence of serious adverse reactions. Mycophenolate mofetil was added as adjunctive therapy due to lack of response to azathioprine.